A high-performance line-start permanent magnet synchronous motor amended from a small industrial three-phase induction motor - Fei, Wei-Zhong; Luk, Patrick Chi-Kwong; Ma, J.; Shen, Jian-Xin; Yang, G. (Cranfield University, 2009)
Small industrial three-phase induction motors (IMs) normally suffer from poor operational efficiency and power factor. This paper presents a high-performance line-start permanent magnet synchronous motor (LSPMSM) which is developed by simple modifications of an off-the-shelf small industrial three-phase IM with minimized additional costs. Two-dimensional (2-D) dynamic finite element analysis (FEA) models are employed to assess the machine performances, which are validated by comprehensive experimental results. The experimental comparisons between the amended LSPMSM and the original IM have indicated that significant improvements in efficiency and power factor can be achieved by the proposed LSPMSM.
Keywords: Line-start induction machine permanent magnet synchronous motor power factor improvement dynamic finite element analysis design